iNO therapy in patients with congenital diaphragmatic hernia: discrepancy between widespread use and therapeutic effects = iNO Therapie bei Patienten mit angeborener Zwerchfellhernie : Diskrepanz zwischen Anwendungshäufigkeit und therapeutischen Effekten - Herich, Kira; Schaible, Thomas; Reinhard, Julia; Rafat, Neysan; Otto, Christiane; Büttner, Sylvia; Lange, Bettina (Klinische Pädiatrie, 2019)
Background: Despite recent studies failing to prove beneficial effects of iNO therapy in patients with CDH, its use is still widespread. The aim of this work was to analyze iNO use in a retrospective cohort focusing on outcome parameters. Patients 378 CDH patients born and treated in Mannheim University Medical Center, Department for Neonatology, between 2010 and 2017 constituted our cohort. Therapy was based on the standardized protocol of the CDH EURO Consortium. Method: General data (sex, birth weight, gestational age etc.) and therapy-related data (duration of iNO application, OI after 60 mins, need for ECMO support etc.) were collected from clinical reports and then conducted using SAS for both mono- and multivariate analyses. Results: Out of 378 newborns with CDH, 265 received iNO (70.1%), of whom 82 (30.9%) showed a significant OI reduction of ≥5 pts after 60 mins (=responders), median OI improved by 1.85 pts overall. Among initial responders iNO, application reduced the need for ECMO support (p=0.0054), increased the time to ECMO initiation (p=0.005) and reduced mortality (p=0.0396). Discussion: A group of 43 patients considerably benefited from iNO and thererfore as they did not need ECMO support. Even though iNO therapy has failed to prove significant beneficial effects for non-responders, the application is still to be considered an essential treatment method in the transitional period of CDH patients. Conclusions: A more critical approach towards iNO application in nonresponders should be promoted. Further extensive multicenter studies on treatment alternatives for CDH-PAH are desirable.
Gesehen am 19.02.2020